CXCL4 is a novel inducer of human Th17 cells and correlates with IL‐17 and IL‐22 in psoriatic arthritis. Issue 3 (15th January 2018) - Affandi, Alsya J.; Silva‐Cardoso, Sandra C.; Garcia, Samuel; Leijten, Emmerik F. A.; van Kempen, Tessa S.; Marut, Wioleta; van Roon, Joel A. G.; Radstake, Timothy R. D. J.
Abstract: CXCL4 regulates multiple facets of the immune response and is highly upregulated in various Th17‐associated rheumatic diseases. However, whether CXCL4 plays a direct role in the induction of IL‐17 production by human CD4 + T cells is currently unclear. Here, we demonstrated that CXCL4 induced human CD4 + T cells to secrete IL‐17 that co‐expressed IFN‐γ and IL‐22, and differentiated naïve CD4 + T cells to become Th17‐cytokine producing cells. In a co‐culture system of human CD4 + T cells with monocytes or myeloid dendritic cells, CXCL4 induced IL‐17 production upon triggering by superantigen. Moreover, when monocyte‐derived dendritic cells were differentiated in the presence of CXCL4, they orchestrated increased levels of IL‐17, IFN‐γ, and proliferation by CD4 + T cells. Furthermore, the CXCL4 levels in synovial fluid from psoriatic arthritis patients strongly correlated with IL‐17 and IL‐22 levels. A similar response to CXCL4 of enhanced IL‐17 production by CD4 + T cells was also observed in patients with psoriatic arthritis. Altogether, we demonstrate that CXCL4 boosts pro‐inflammatory cytokine production especially IL‐17 by human CD4 + T cells, either by acting directly or indirectly via myeloid antigen presenting cells, implicating a role for CXCL4 in PsA pathology. Abstract : CXCL4 is highly increased in autoimmune and inflammatory disorders. Here we show that CXCL4 directs activated human CD4 + T cells toward Th17 cells, by acting directly or indirectly via antigen presenting cells, in healthy and psoriatic arthritis patients. Our findings implicate a novel role for CXCL4 as a Th17 driver.